Altered Blood Gene Expression of Tumor-Related Genes (PRKCB, BECN1, and CDKN2A) in Alzheimer’s Disease - Antonell, Anna; Lladó, Albert; Sánchez-Valle, Raquel; Sanfeliu, Coral; Casserras, Teresa; Rami, Lorena; Muñoz-García, Cristina; Dangla-Valls, Adrià; Balasa, Mircea; Boya, Patricia; Kalko, Susana G; Molinuevo, José Luis (Molecular neurobiology, 2016)
Alzheimer’s disease (AD) is the most common of the neurodegenerative diseases. Recent diagnostic criteria have defined a preclinical disease phase during which neuropathological substrates are thought to be present in the brain. There is an urgent need to find measurable alterations in this phase as well as a good peripheral biomarker in the blood. We selected a cohort of 100 subjects (controls = 47; preclinical AD = 11; patients with AD = 42) and analyzed whole blood expression of 20 genes by quantitative polymerase chain reaction. The selected genes belonged to calcium signaling, senescence and autophagy, and mitochondria/oxidative stress pathways. Additionally, two genes associated with an increased risk of developing AD (clusterin ( CLU ) and bridging integrator 1 ( BIN1 )) were also analyzed. We detected significantly different gene expressions of BECN1 and PRKCB between the control and the AD groups and of CDKN2A between the control and the preclinical AD groups. Notably, these three genes are also considered tumor suppressor ( CDKN2A and BECN1 ) or tumor promoter ( PRKCB ) genes. Gene-gene expression Pearson correlations were computed separately for controls and patients with AD. The significant correlations ( p < 0.001) were represented in a network analysis with Cytoscape tool, which suggested an uncoupling of mitochondria-related genes in AD group. Whole blood is emerging as a valuable tissue in the study of the physiopathology of AD.